Health and Social Factors Related to Tobacco Cultivation: a Literature Review - เพ็ชรภูมิ, จักรพันธ์; คงเจริญ, วิชาดา (Journal of Health Science of Thailand, 2024)
The World Health Organization Framework Convention on Tobacco Control or WHO FCTC, is a framework of an agreement aimed at protecting the population from the harmful effects of tobacco consumption and secondhand smoke exposure. Thailand as one of the countries that participated in ratifying this framework and need to respond by achieving the specified goals. In the past, it has been found that Thailand still has limited empirical evidence related to Article 18 on environmental protection and the health of individuals related to tobacco cultivation and production. This article aimed to review original research articles on the impact of tobacco cultivation both internationally and domestically, and identify research gaps in Thailand by collecting data from research articles related to the WHO FCTC Article 18 published in electronic databases generated 559 articles. There were 37 articles met the criteria for inclusion in the final analysis. The study concluded that all original research articles focus on four main areas which include physical health impacts, mental health impacts, quality of life impacts, and environmental impacts. In Thailand, there was a lack of research on the mental health impacts of tobacco farmers and environmental impacts. These research gaps may lead to a lack of comprehensive empirical evidence that is a concrete result of tobacco cultivation and production in Thailand. Therefore, the Tobacco Control Research and Knowledge Management Center should prioritize research topics that are still missing to address these research gaps in the future.